THE ROLE OF MUSLIM WOMEN IN THE GLOBAL ECONOMY: OPPORTUNITIES, CHALLENGES, AND CONTRIBUTIONS IN THE CONTEMPORARY ERA - Arinal Alviqri Aritonang; Khairani Hayat Situmorang (CV. Barokah Publsiher, 2026)
This article examines the multidimensional role of Muslim women in the contemporary global economy, with particular attention to the interplay between religious identity, economic participation, and sociopolitical structures. Drawing on empirical data, case studies, and theoretical frameworks from Islamic economics and gender studies, this study identifies key opportunities available to Muslim women in the 21st century—including the growth of the Islamic finance sector, digital entrepreneurship, and international trade in modest fashion and halal industries. At the same time, the article critically addresses persistent structural and cultural challenges such as gender-based discrimination, limited access to education and capital, and the misinterpretation of Islamic teachings that restrict women's economic agency. The study further highlights the significant contributions of Muslim women as entrepreneurs, professionals, policymakers, and social innovators across diverse global contexts. Employing a qualitative-descriptive methodology, the findings suggest that when supported by enabling institutional environments, Islamic values can serve as a catalyst—rather than a barrier—to women's economic empowerment. This paper calls for a reorientation of policy, scholarship, and Islamic discourse toward a more inclusive and equity- driven paradigm of Muslim women's economic participation.